Mecanismos de resistência do meloeiro ao ácaro Tetranychus urticae Koch (Acari: Tetranychidae) e ecologia química da interação cajueiro, praga e inimigo natural - Saraiva, Wenner Vinicius Araújo (2024)
The cashew tree (Anacardium occidentale L.) and the melon tree (Cucumis melo L.) are fruit trees of social and economic importance for northeastern farmers in semi-arid regions. In both crops, damage caused by insect pests is among the factors that most affect production. While in the cashew tree, damage caused by the whitefly Aleurodicus cocois causes negative impacts on nut production, in the melon tree, population outbreaks of Tetranychus urticae can reduce fruit yields. The objectives of this work were to determine the biological aspects (oviposition rate and population growth), food preference and the relationship between leaf morphology characteristics of four melon genotypes and resistance to T. urticae; as well as evaluating the olfactory response of C. externa to cashew tree volatiles induced by A. cocois herbivory, identifying cashew tree volatiles induced by A. cocois herbivory and evaluating the development of C. externa when fed A. cocois. Regarding the results, the melon tree, in trials with and without choice, CNPH 06–1047-343, CNPH 11–1071-43 and CNPH 06-1047-341 presented a lower number of T. urticae eggs when compared to the susceptible hybrid Goldex. Furthermore, in these genotypes the mite underwent changes related to its development cycle. Among the morphological characters, the density of trichomes, the thickness of the epidermis and the mesophyll influenced the resistance of the melon against T. urticae. Furthermore, C. externa was attracted to cashew plant volatiles infested by A. cocois. According to the volatile profiles analyzed α-fellandrene, α-terpinene, ρ-mentha-2,4(8)-diene, β-caryophyllene and germacrene D were released in large quantities by the Embrapa 51 genotype only after infestation. Although the development time and survival of some immature stages of C. externa varied with the type of prey, the predator was able to complete its egg-adult development cycle when fed on A. cocois. In conclusion, the genotypes CNPH 06–1047-343, CNPH 11–1071-43 and CNPH 06-1047-341 have resistance against T. urticae. The greater thickness of the leaf epidermis and mesophyll reduces the viability of immatures and the population growth rate of T. urticae in these genotypes. the generalist predator C. externa is capable of distinguishing and selecting plants of the Embrapa 51 cashew genotype infested by A. cocois through volatile signals. The volatile profile analysis provides information on the compounds involved in the attractiveness behavior of C. externa to Embrapa 51 volatiles infested by A. cocois (α-fellandrene, α-terpinene, ρ-mentha-2,4(8)-diene , β-caryophyllene and germacrene D). Additionally, under laboratory conditions, C. externa completes the life cycle when fed with A. cocois and A. kuehniella eggs. However, A. cocois allows for slower development and lower survival.